Provider Perceptions and Domestic Violence (DV) Survivor Experiences of Traumatic and Anoxic-Hypoxic Brain Injury: Implications for DV Advocacy Service Provision. Issue 6 (3rd July 2019) - Nemeth, Julianna M.; Mengo, Cecilia; Kulow, Emily; Brown, Alexandra; Ramirez, Rachel
ABSTRACT: Domestic violence (DV) survivors are susceptible to traumatic and anoxic-hypoxic brain injury, collectively referred to as brain injury (BI). This study characterized: 1) provider perception of the impact of BI on DV survivors' experiences with advocacy services and 2) survivors' reported exposures that can lead to BI. Data were collected at five advocacy organizations in 2017: 11 focus groups were conducted with service providers (n = 45 staff & 17 administrators) and interview administered surveys were completed with survivors (n = 49). Our findings indicate a discrepancy between providers' perception of the potential impact of BI on survivors' presentation and ability to access services, and survivors' pervasive exposure to incidents that can cause BI. Over 81% of survivors reported having been hit in the head or been made to have their head hit another object at least once, and over 83% of survivors reported ever having been strangled. Raising organizational capacity to serve DV survivors with BI is necessary. Intervention suggestions are provided.